Multinational firms the global-local dilemma - Dunning, John H.; Mucchielli, Jean Louis (Studies in global competition, 2002)
This volume presents the work of specialists on multinational strategy, addressing the main questions of globalization, competitiveness, the impact of regionalism, agglomeration, strategic location choice, and relocation and public aid.